Model Fikir–Cakap–Tulis dalam Pembelajaran Menulis Cerita Pendek - Suryanti (Jurnal Sociohumaniora Kodepena (JSK), 2020)
Abstract This study aims to determine differences in short short writing skills that are significant between students who take part in learning using the Thinking - Proficient - Write model and students who take part in learning without using the Thinking-Write-Writing model, as well as testing the effectiveness of the written-thinking models in learning to write Short stories of class X students of SMA Negeri 4 Baubau City. This research is an experimental research with protest-posttest group design. The variables in this study are independent variables, namely Think-Talk-Write, and the dependent variable is short story writing skills. The population in this study were all grade X students of SMA Negeri 4 Baubau. The sample used in this study amounted to two classes, with the division of one class as a control class and one class as an experimental group. Samples were determined using cluster random sampling techniques. From the determination using cluster random sampling technique, it was obtained X-6 class as an experimental group, and X-9 class as a control class. Date collection techniques using the test, in the form of a short story writing test. Date analysis techniques were performed using pretest and posttest with t-test. The results of this study indicate that there are significant differences in short story writing skills between students who take part in learning by using written-thinking models and students who take lessons without using written-thinking models. This is evident from the t-test on the pretest and posttest scores of the experimental group resulting in a tcount of 13,356 with a df (degree of freedom) of 31 and a value of P = 0,000. In addition, the results of the t test showed that the effective writing-literacy model was used in learning to write short stories, because P ˂ 0.05 = significant. Keywords: Proficient-Write, short story writing skills.